Case report: Bladder preserving after maximal transurethral resection of the bladder tumor combined with chemotherapy and immunotherapy in recurrent muscle-invasive bladder cancer patients: A report of two cases - Mao, Jiaquan; Yang, Chunguang; Xin, Sheng; Cui, Kai; Liu, Zheng; Wang, Tao; Hu, Zhiquan; Wang, Shaogang; Liu, Jihong; Song, Xiaodong; Song, Wen (Frontiers in Medicine, 2022)
Background Radical cystectomy (RC) with postoperative concurrent radiotherapy is the preferred treatment option for muscle-invasive bladder cancer (MIBC). However, some patients are unable to tolerate RC or may have postoperative complications after RC and most patients require bladder-preserving treatment. There are no reports on the efficacy of maximal transurethral resection of the bladder tumor (TURBT) in combination with chemotherapy plus tislelizumab for bladder preservation in recurrent MIBC patients. Case presentation We report two cases diagnosed with recurrent MIBC who achieved pathological complete response (pCR) and bladder preservation after maximal TURBT combined with chemotherapy plus tislelizumab. Conclusion Postoperative immunotherapy should be considered for all patients with recurrent MIBC who are eligible for immunotherapy. In addition, high programmed death ligand-1 (PD-L1) expression, high tumor mutation burden (TMB), and TP53 mutation level can be combined to predict tislelizumab efficacy.